Individual‐ and neighborhood‐level socioeconomic status and risk of aggressive breast cancer subtypes in a pooled cohort of women from Kaiser Permanente Northern California. Issue 24 (20th August 2021) - Aoki, Rhonda‐Lee F.; Uong, Stephen P.; Gomez, Scarlett Lin; Alexeeff, Stacey E.; Caan, Bette J.; Kushi, Lawrence H.; Torres, Jacqueline M.; Guan, Alice; Canchola, Alison J.; Morey, Brittany N.; Lin, Katherine; Kroenke, Candyce H.
Abstract : Background: Low socioeconomic status (SES) has been associated with a higher risk of aggressive breast cancer (BC) subtypes, but few studies have examined the independent effects of both neighborhood‐level socioeconomic status (nSES) and individual‐level SES measures. Methods: This study included 5547 women from the Pathways and Life After Cancer Epidemiology cohorts who were diagnosed with invasive BC. Generalized estimating equation models were used to examine associations of nSES (a composite score based on income, poverty, education, occupation, employment, rent, and house value) and individual‐level SES (income and education) with BC subtypes: luminal B (LumB), Her2‐enriched (Her2‐e), and triple‐negative breast cancer (TNBC) relative to luminal A (LumA). Models controlled for age, race, nativity, stage, days from diagnosis to survey, and study cohort and simultaneously for nSES and individual‐level SES. Results: In fully adjusted models, low nSES was significantly associated with the LumB (odds ratio for quartile 1 vs quartile 4 [ORQ1vQ4 ], 1.31; 95% confidence interval [CI], 1.11‐1.54; P for trend = .005) and TNBC subtypes (ORQ1vQ4, 1.32; 95% CI, 1.02‐1.71; P for trend = .037) relative to LumA. Conversely, individual education was significantly associated with only the Her2‐e subtype (odds ratio for high school degree or less vs postgraduate, 1.68; 95% CI, 1.03‐2.75; P for trend = .030) relative to LumA. Individual income was not significantly associated with any BC subtype. Conclusions: nSES and individual‐level SES are independently associated with different BC subtypes; specifically, low nSES and individual‐level education are independent predictors of more aggressive BC subtypes relative to LumA. Abstract : Low neighborhood‐level socioeconomic status and individual‐level education are independent predictors of more aggressive breast cancer subtypes relative to luminal A.